Pendidikan Karakter Dalam Al Qur’an Pada Kalangan Remaja Di Era Digital - Hartono, Hartono (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2018)
Character education is a process that always leads to continuous improvement in human character in the digital age. Family and educational institutions are a forum that has an important role in the formation of character education in the midst of society, especially among students. This is in accordance with the national education goals, namely to develop the potential of students to become human beings who believe and fear the Almighty God, are noble, healthy, knowledgeable, creative, independent and dignified.